Reinterpreting and Reforming the City: Patrimonialization, Cosmopolitanisms, and the Ethnography of the Heritage-Scape in Damascus - Copertino, Domenico (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2013)
Concepts and practices of patrimonialisation in the Middle East, although primarily imported from Europe during the last phase of Ottoman rule and the colonial mandate/period, have been reinterpreted and given new meanings and aims in the postcolonial era. I investigate a local re-conceptualisation of heritage practice, put forward by Damascenes involved in the heritage policies of Syria’s capital city. I also focus on the marginalisation of groups of people considered unfit to be part of the heritage, which is a common outcome of patrimonialisation. Finally, I explore some questions related to the ethnographical study of the global social spaces that are frequently labeled as “heritage-scapes.”